Thermoelectric properties and cost optimization of spark plasma sintered n-type Si0.9Ge0.1 - Mg2Si nanocomposites. (15th March 2018) - Usenko, Andrey; Moskovskikh, Dmitry; Korotitskiy, Andrey; Gorshenkov, Mikhail; Zakharova, Elena; Fedorov, Aleksandr; Parkhomenko, Yury; Khovaylo, Vladimir
Abstract: We report on thermoelectric properties of low Ge content n -type Si0.9 Ge0.1 –Mg2 Si nanocomposite. Introduction of the Mg2 Si phase into a SiGe matrix resulted in a dramatic drop of the lattice thermal conductivity beyond the previously reported lowest limit for SiGe alloys due to intensification of phonon scattering on SiGe–Mg2 Si grain boundaries. For a sample doped with 1 at.% of Mg2 Si, the peak value of thermoelectric figure of merit ZT reached 0.8 at 800 °C. Sintered nanocomposites still exhibit high thermoelectric performance while being almost two times cheaper than Si0.8 Ge0.2 . Graphical abstract: Image 1